The Effectiveness of Combined Deep-Breathing Relaxation and Endorphin Massage in Reducing Pain and Anxiety During the Active Phase of the First Stage of Labor - Via Zakiah; Juli Purnama Hamudi; Harni Harni (Newinera Publisher, 2026)
Pain and anxiety during the active phase of the first stage of labor may increase physiological stress responses and potentially interfere with labor progress. Complementary therapies, including deep breathing relaxation and endorphin massage, have been widely used as non-pharmacological approaches to improve maternal comfort. To analyze the effectiveness of a complementary therapy combining deep breathing relaxation and endorphin massage in managing pain and anxiety during the active phase of the first stage of labor. A quasi-experimental study with a pretest-posttest control group design was conducted from January to March 2026 in the coastal area of Kendari City, Southeast Sulawesi, Indonesia. A total of 30 participants were recruited using purposive sampling and divided into an intervention group (n=15) and a control group (n=15). Pain intensity was assessed using the Numeric Rating Scale (NRS), while anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). The intervention group demonstrated a significant reduction in pain intensity from 7.80 to 4.20 (p=0.000) and in anxiety levels from 26.5 to 18.3 (p=0.000). The mean reduction in pain (3.60 ± 0.75) and anxiety (8.20 ± 1.90) was significantly greater than that observed in the control group (p = 0.000). The combination of deep breathing relaxation and endorphin massage is an effective complementary therapy for reducing pain intensity and anxiety during the active phase of the first stage of labor and may be integrated into routine maternity care.